2017
DOI: 10.1016/j.jvs.2016.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the stromal vascular fraction of adipose tissue as the basis for a stem cell-based tissue-engineered vascular graft

Abstract: Objective One of the rate-limiting barriers within the field of vascular tissue engineering is the lengthy fabrication time associated with expanding appropriate cell types in culture. One particularly attractive cell type for this purpose is the adipose-derived mesenchymal stem cell (AD-MSC), which is abundant and easily harvested from liposuction procedures. However, even this cell type has its drawbacks including the required culture period for expansion which could pose risks of cellular transformation or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 36 publications
0
41
0
1
Order By: Relevance
“…Bone marrow derived MSCs (BM-MSCs), purified from BM-MNCs, have demonstrated favorable preclinical findings in TEVGs ( 45 47 ). Similarly, adipose derived MSCs (ADMSCs) ( 48 , 55 ) and muscle derived MSCs ( 49 , 56 ) have been used in TEVG studies. Studies employing pericytes are also included in this review ( 50 ) as they have been shown to express MSC markers and display the capacity for tri-lineage differentiation [as reviewed in Crisan et al ( 57 )].…”
Section: Stem Cell Based Tevg Studiesmentioning
confidence: 99%
“…Bone marrow derived MSCs (BM-MSCs), purified from BM-MNCs, have demonstrated favorable preclinical findings in TEVGs ( 45 47 ). Similarly, adipose derived MSCs (ADMSCs) ( 48 , 55 ) and muscle derived MSCs ( 49 , 56 ) have been used in TEVG studies. Studies employing pericytes are also included in this review ( 50 ) as they have been shown to express MSC markers and display the capacity for tri-lineage differentiation [as reviewed in Crisan et al ( 57 )].…”
Section: Stem Cell Based Tevg Studiesmentioning
confidence: 99%
“…For instance, MSCs regulate chemotaxis, activation, function, and survival of neutrophils via an IL-6-STAT3-ERK1/2 signaling cascade in gastric cancer and related solid cancers 99,131 . These MSC-primed neutrophils promote the differentiation of normal MSCs into CAFs 131 .…”
Section: Mscs and Tumor Microenvironmentmentioning
confidence: 99%
“…The design of our novel bulk seeding device for large, "human-sized" scaffolds was first conceived during the doctoral dissertation work of Soletti (2008). It is based on our lab's previously published and validated custom rotational vacuum seeding device which has been used to produce TEVGs for small animal testing (Nieponice et al, 2010;Soletti et al, 2011;Krawiec et al, 2016Krawiec et al, , 2017Haskett et al, 2018). The common concept is to achieve bulk seeding of rotating, porous, tubular scaffolds via local luminal delivery of cells under applied vacuum.…”
Section: Design Of the Translating-rotating Seeding Devicementioning
confidence: 99%
“…The advancement of tissue engineered vascular grafts (TEVGs) in recent years, and their ability to form functional neo-vessels, presents as a promising clinical option for the treatment of vascular disease (Cunnane et al, 2018). TEVGs often incorporate cells into biodegradable scaffolds through various cell-seeding techniques (Villalona et al, 2010;Weinbaum et al, 2020), and the presence of cells has demonstrated improved TEVG patency rates through reduced thrombosis and stenosis (Nieponice et al, 2010;Soletti et al, 2011;Krawiec et al, 2016Krawiec et al, , 2017Haskett et al, 2018).…”
Section: Introductionmentioning
confidence: 99%